Classification of Freshness Levels and Prediction of Changes in Evolution of NH3 and H2S Gases from Chicken Meat during Storage at Room Temperature - Pramilih Nastiti; Nursigit Bintoro; Joko Karyadi; Sri Rahayoe; Darmawan Nugroho (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2022)
Chicken meat has a high nutrient content. However, its quality is easy to be degraded. The degradation is normally characterized by the formation of metabolite gases (NH3 and H2S) as deterioration indicators. Sensors detect phenomena better than human senses. This study aimed to classify meat quality based on gas formation during meat storage. In addition, a kinetics model of gas changes was determined. The gases were detected using a set of equipment consisting of Raspberry Pi and Metal-Oxide-Semiconductor (MOS) gas sensors. Samples were put in a 10 x 10 x 10 (cm) black container. MOS sensors were put inside the box to detect the gases at room temperature for 24 hours, with data collection being recorded every hour. Obtained data were then analyzed using Principle Component Analysis (PCA) for quality classification. The study showed that the quality of chicken meat was classified into three groups with a total variance of more than 95%. PC1 explained 88.2%, and PC2 explained 9.0%. The constant rate of H2S and NH3 changes followed the first-order kinetics with a constant rate of 0.2641 and 0.2925, respectively. The equation for H2S and NH3 changes were Ct=1.70 e0.2641 t and Ct=1.00 e0.2925 t, respectively. Keywords: Chicken meat, Freshness, H2S gas, NH3 gas, Sensor